A new intuitionistic preference scale based on interval type-2 fuzzy set for MCDM problems - Nurnadiah, Zamri; Lazim, Abdullah (World Academic Union, 2015)
Interval Type-2 Fuzzy TOPSIS (IT2FTOPSIS) is a useful way to handle Fuzzy Multiple Attribute Decision Making (FMADM) problems in a more flexible and intelligent manner. It is very useful due to the fact that it uses Type-2 Fuzzy Sets (T2FSs) rather than Type-1 Fuzzy Sets (T1FSs) to represent the evaluating values and the weights of attributes. Besides, all the linguistic terms are pointed in Type-1 Fuzzy Numbers (T1FNs) rather than Fuzzy TOPSIS (FTOPSIS), using crisps numbers. However, IT2FTOPSIS only focuses on the membership degree without considering the non-membership degree. In real life situation, evaluation becomes more comprehensive if non-membership degree is considered concurrently. Preference is expected to be more effective when considering both membership and non-membership degree due to the effectiveness of fuzziness taken from the hesitation degree. Therefore, the aim of this paper is to introduce a new preference scale that considers both membership and non-membership degree in IT2FTOPSIS. Both membership and non-membership degree of Intuitionistic Fuzzy Sets (IFSs) are developed under Interval Type-2 FMADM environment. Then, this new method is tested using five illustrative examples. Finally, this new method is applied to a case study on selecting the best of flood control project and the results demonstrate the feasibility. This paper has been proven able to measure human being decision making progress to solve the incomplete information and becomes a new way to deal with the vagueness and uncertainty.